Angelicone Ameliorates Ulcerative Colitis in Mice via Modulating Gut Microbiota - Ruan, Chengwei; Gao, Weiwei; Wang, Guoguo; Fan, Wenting; Zhang, Weifeng; Tao, Shuang; Wu, Zheng (Planta Medica, 2025)
Ulcerative colitis (UC) is a persistent, periodically reoccurring inflammatory condition that impacts the gastrointestinal tract. Angelicone, a principal compound extracted from Angelica sinensis, may offer a potential alternative therapeutic approach for UC through the downregulation of inflammatory mediators. Nonetheless, the pharmacological impacts and molecular pathways of angelicone in UC management, particularly in relation to gut microbiota, remain unexplored. The current study scrutinized the modifications in gut microbiota in mice afflicted with UC, induced by 3% dextran sodium sulfate (DSS), utilizing 16S rRNA sequencing. The study demonstrated that angelicone substantially enhanced clinical indices, mitigated colonic damage, decreased cytokine levels, and reestablished the integrity of the intestinal epithelial barrier in UC mice. Furthermore, we discerned distinct bacterial genera that were responsive to angelicone treatment. Importantly, angelicone augmented the abundance of gut microbiota and partially reinstated the disrupted intestinal microbial composition, inclusive of the phyla Proteobacteria, Firmicutes, and Bacteroidetes. To summarize, our research offers novel perspectives into the intervention mechanisms of angelicone in the treatment of UC.
Keywords: angelicone; gut microbiota; ulcerative colitis; dextran sodium sulfate; 16S rRNA; Angelica sinensis; Apiaceae